Technē. - Tuckwell, Jason (Philosophy Today, 2019)
This essay re-problematises the Aristotelian concept of techne in terms of the mathematical function to demonstrate the centrality of agency in technics. This schema animates computational theory as an agential operator or computer, to situate agency's necessity to the technical apparatus and the production of abstract relations.